Therapeutic Targeting of Neutrophil Extracellular Traps in Atherogenic Inflammation - Van Avondt, Kristof; Maegdefessel, Lars; Soehnlein, Oliver (Thrombosis and Haemostasis, 2019)
Neutrophils and neutrophil extracellular traps (NETs) have a robust relationship with atherothrombotic disease risk, which led to the idea that interfering with the release of NETs therapeutically would ameliorate atherosclerosis. In human studies, acute coronary events and the pro-thrombotic state cause markedly elevated levels of circulating deoxyribonucleic acid (DNA) and chromatin, suggesting that DNase I might produce cardiovascular benefit. DNase I reproduced the phenotype of peptidylarginine deiminase 4 (PAD4) deficiency and showed a significant benefit for atherothrombotic disease in experimental mouse models. However, the mechanisms of benefit remain unclear. Insights into the mechanisms underlying NET release and atherogenic inflammation have come from transgenic mouse studies. In particular, the importance of neutrophil NET formation in promoting atherothrombotic disease has been shown and linked to profound pro-inflammatory and pro-thrombotic effects, complement activation and endothelial dysfunction. Recent studies have shown that myeloid deficiency of PAD4 leads to diminished NET formation, which in turn protects against atherosclerosis burden, propagation of its thrombotic complications and notably macrophage inflammation in plaques. In addition, oxidative stress and neutrophil cholesterol accumulation have emerged as important factors driving NET release, likely involving mitochondrial reactive oxidants and neutrophil inflammasome activation. Further elucidation of the mechanisms linking hyperlipidaemia to the release of NETs may lead to the development of new therapeutics specifically targeting atherogenic inflammation, with likely benefit for cardiovascular diseases.
Keywords: neutrophil; NETosis; atherogenic inflammation; atherothrombotic disease